2015
DOI: 10.2147/ijn.s92596
|View full text |Cite|
|
Sign up to set email alerts
|

Enhanced detection of single-cell-secreted proteins using a fluorescent immunoassay on the protein-G-terminated glass substrate

Abstract: We present an evaluation of protein-G-terminated glass slides that may contain a suitable substrate for aligning the orientation of antibodies to obtain better binding moiety to the target antigen. The results of the protein-G-terminated slides were compared with those obtained with epoxy-based slides to evaluate signal enhancement for human immunoglobulin G (IgG) targets, and an increase in the average fluorescence intensity was observed for the lowest measurable amount of IgG target in the assay using protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Studies have shown that the content of the loaded antigen in well-oriented antibodies is at least 3 times higher than the randomly-oriented antibodies 7,8 . Besides, it has been demonstrated that glass slides coated with the PrG could be used as a suitable substrate to orient the antibodies resulting in the detection of low concentration of antigens 9 . Furthermore, it was shown that using the PrG-coupled beads significantly improved the multiplex immunoassay approach and simultaneously quantified analytes in a limited volume 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the content of the loaded antigen in well-oriented antibodies is at least 3 times higher than the randomly-oriented antibodies 7,8 . Besides, it has been demonstrated that glass slides coated with the PrG could be used as a suitable substrate to orient the antibodies resulting in the detection of low concentration of antigens 9 . Furthermore, it was shown that using the PrG-coupled beads significantly improved the multiplex immunoassay approach and simultaneously quantified analytes in a limited volume 10 .…”
Section: Introductionmentioning
confidence: 99%